The factors impacting employee commitment to organizational change - Petrauskaitė-Jocienė, Vaida; Korsakienė, Renata (Business: Theory and Practice, 2024)
In the financial sector, the need for organizational change is impacted by the consequences of pandemic, changes in consumer needs, competition, climate change, and increasing number of financial technology start-ups. The banks play a vital role in the economies of countries, so the changes taking place in them are undoubtedly important, and the commitment of employees to change is considered a necessary condition for the successful implementation of change. However, the studies, investigating how different factors contribute to the employees’ commitment to change in the Lithuanian banking sector, are scant. Therefore, the aim of this article is to determine how transformational leadership style, organizational change goals, communication quality, and certainty affect employees’ commitment to change in banking sector organization. The results of the study demonstrate that transformational leadership style, quality of change communication, clarity of goals, and certainty increase employees’ commitment to change, and transformational leadership style increases employees’ commitment to change by acting as a mediator between organizational communication, clarity of organizational change goals, and other information that increases employees’ feeling of certainty. The findings provide insights for managers who want to support employees and seek the success of organizational changes.